Meretas Meretas Pemilih Berkelas dalam Pemilu - Sutiyo Sutiyo (Indonesian Community Service and Empowerment Journal (IComSE), 2021)
MERETAS PEMILIH BERKELAS DALAM PEMILU SUTIYO1* Prodi Ilmu Administrasi Publik, Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Dharma Wacana1* Jl. Kenanga No.3 Mulyojati, Metro Barat 16C Kota Metro-Lampung Email: tiodharma@yahoo.com ABSTRACT Elections as a means of election or circulation of public leadership are facing challenges from the quality factor of voters, as is the case with money politics. In such circumstances, the purpose of writing this outreach activity is an effort to hack classy voters. The method of community service activities is carried out through the presentation of the material along with a question and answer session or discussion. Technically, the community service in the field is assisted by village officials and students in mobilizing audiences and completing the facilities and infrastructure for the event. In brief, from the discussion of the activities, it was revealed that the residents, especially those living in the village, really need this kind of activity. Counseling becomes a medium and a source of reference for improving the quality of voters in elections, which they have not received much so far. In this case, the audience absorbs new things that are valuable for improving the quality of choices, such as regarding the quality of political parties and public leadership. The conclusion from this outreach activity is that the rationality / objectivity aspect of elections in the eyes of citizens has so far been less popular with the practice of money politics. On the one hand, there is not much information or material regarding efforts to improve the quality of voters.As for the other side, the General Elections have not been optimal in presenting quality election contestants / participants, both in terms of candidates and political parties. The impact of this outreach activity is to become a strategic and important means of igniting the determination of citizens in the context of improving the quality of voters. Keywords: general election, election effectiveness, voter quality